Improved triple-module fluorescent biosensor for the rapid and ultrasensitive detection of Campylobacter jejuni in livestock and dairy. (July 2022) - Cheng, Xiaohong; Liu, Weixing; Wang, Zhuangzhuang; Yang, Rongxue; Yu, Lejun; Du, Qingbao; Ge, Anshan; Liu, Chenguang; Chi, Zhe
Abstract: Campylobacter jejuni ( C. jejuni ) is a major pathogen responsible for the food-borne illness, campylobacteriosis. To comply with regulatory requirements, its total concentration in food and animal feces must be extremely low. As a result, monitoring this bacterium requires an immediate and cost-effective approach that meets the requirements of the food and livestock industries. The current study reports the development of an improved biosensor comprising three modules viz. a novel transducing module (1), a bi-functional binding/actuating module (2), and an enrichment module (3), synthesized using commercially available components. Module 3, composed of magnetic beads functionalized with a C. jejuni -specific aptamer, utilizes magnetic separation to isolate and enrich C. jejuni from samples. The resulting module 3– C. jejuni complexes can bind module 2 copolymer to form ternary complexes. When these ternary complexes are separated and reacted with module 1, composed of a ferric ion/fluorescein sodium (Fe 3+ /FLNa) pair, they chelate Fe 3+ ions, resulting in the recovery of FLNa after magnetic separation via fluorescence. The as-synthesized biosensor demonstrated a high sensitivity range of 10–10 7 CFU/mL, and a detection limit of 3 CFU/mL. Additionally, microfluidics was used to eliminate interferences resulting from the module 3-enriched products, while detecting C. jejuni in real-world samples. Herein, the biosensor demonstrated an actual limit of detection (LOD) of 10 1 CFU/mL within ≈60 min. Thus, the biosensor and the assisting treatments offer a rapid and ultrasensitive platform for detecting C. jejuni in livestock and dairy industries, outperforming conventional approaches. Highlights: A biosensing technqiue is presented for C. jejuni ultrasensitive detection. The biosensing has a detection range of 10–10 7 CFU/mL and a limit of 3 CFU/mL. Proteinase and microfluidics enable the detection of C. jejuni in real samples.